ACADEMIC EXPERIENCES AND LIBERATING EXPECTATIONS IN FOREIGN LANGUAGE TEACHING - Ulloa Aguilar, Renato (2024)
The objective of this essay is to reflect on different academicexperiences, as well as the essential aspects present during the different teacher training processes, especially foreign language teachers, from a liberating and affective perspective.